Anti-Virulence Therapeutic Approaches for Neisseria gonorrhoeae - Katherine Y. L. Lim; Christopher A. Mullally; Ethan C. Haese; Emily A. Kibble; Nicolie R. McCluskey; Edward C. Mikucki; Van C. Thai; Keith A. Stubbs; Mitali Sarkar-Tyson; Charlene M. Kahler (MDPI AG, 2021)
While antimicrobial resistance (AMR) is seen in both Neisseria gonorrhoeae and Neisseria meningitidis, the former has become resistant to commonly available over-the-counter antibiotic treatments. It is imperative then to develop new therapies that combat current AMR isolates whilst also circumventing the pathways leading to the development of AMR. This review highlights the growing research interest in developing anti-virulence therapies (AVTs) which are directed towards inhibiting virulence factors to prevent infection. By targeting virulence factors that are not essential for gonococcal survival, it is hypothesized that this will impart a smaller selective pressure for the emergence of resistance in the pathogen and in the microbiome, thus avoiding AMR development to the anti-infective. This review summates the current basis of numerous anti-virulence strategies being explored for N. gonorrhoeae.